2008
DOI: 10.1097/hjh.0b013e3283015e5a
|View full text |Cite
|
Sign up to set email alerts
|

EVAluation of the prognostic value of BARoreflex sensitivity in hypertensive patients: the EVABAR study

Abstract: Reduction in baroreflex sensitivity marked by a reduction in vagal reflexes is an independent marker of the risk of mortality and major adverse cardiovascular events in hypertensive patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 25 publications
1
58
0
5
Order By: Relevance
“…Indeed, experimental and clinical studies have extensively documented the health benefits of exercise training in hypertensive subjects. In untreated hypertensive subjects, Laterza et al (26) observed normalized baroreflex function and peripheral sympathetic nerve activity after exercise training, which are closely related to end-organ injuries (27) and cardiovascular mortality (35) in hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, experimental and clinical studies have extensively documented the health benefits of exercise training in hypertensive subjects. In untreated hypertensive subjects, Laterza et al (26) observed normalized baroreflex function and peripheral sympathetic nerve activity after exercise training, which are closely related to end-organ injuries (27) and cardiovascular mortality (35) in hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that depressed BRS (\3 ms/mm Hg) identifies, independently of age, a subgroup at long-term high risk of cardiovascular mortality in post-myocardial infarction patients [24]. Ormezzano et al [25] have recently shown that baroreflex sensitivity under 4.5 ms/mmHg was associated with an increased relative risk of 2.5 of major adverse cardiovascular events in hypertensive patients.…”
Section: Heart Rate Variabilitymentioning
confidence: 98%
“…Importantly, low baroreflex sensitivity is an independent predictor of mortality and major adverse cardiovascular-related events in hypertensive patients. 43 Improvements in baroreflex function after RDN may, therefore, directly improve mortality risk in these patients. This might be related to improvements in BP lability/variability, 44 a known risk for target organ damage, including stroke incidence.…”
Section: Cardiac and Sympathetic Baroreflex Sensitivitymentioning
confidence: 99%